Brain Region-Dependent Effects of Neuropeptide Y on Conditioned Social Fear and Anxiety-Like Behavior in Male Mice - Kornhuber, Johannes (Int J Mol Sci, 2021)
Neuropeptide Y (NPY) has anxiolytic-like effects and facilitates the extinction of cued and contextual fear in rodents. We have previously shown that the intracerebroventricular administration of NPY reduces the expression of social fear in a mouse model of social fear conditioning (SFC). In the present study, we aimed to identify the brain regions that mediate these effects of NPY. We show that NPY (0.1 nmol/0.2 µL/side) reduces the expression of SFC-induced social fear in a brain-region-dependent manner. In more detail, NPY reduced the expression of social fear when administered into the dorsolateral septum (DLS) and central amygdala (CeA), but not when administered into the dorsal hippocampus (DH), medial amygdala (MeA) and basolateral amygdala (BLA). We also investigated whether the reduced expression of social fear might partly be due to a reduced anxiety-like behavior, and showed that NPY exerted anxiolytic-like effects when administered into the DH, DLS, CeA and BLA, but not when administered into the MeA. This study identifies the DLS and the CeA as brain regions mediating the effects of NPY on the expression of social fear and suggests that partly distinct neural circuitries mediate the effects of NPY on the expression of social fear and on anxiety-like behavior.